2021
DOI: 10.3390/antibiotics10050577
|View full text |Cite
|
Sign up to set email alerts
|

A New Twist: The Combination of Sulbactam/Avibactam Enhances Sulbactam Activity against Carbapenem-Resistant Acinetobacter baumannii (CRAB) Isolates

Abstract: An increasing number of untreatable infections are recorded every year. Many studies have focused their efforts on developing new β-lactamase inhibitors to treat multi-drug resistant (MDR) isolates. In the present study, sulbactam/avibactam and sulbactam/relebactam combination were tested against 187 multi-drug resistant (MDR) Acinetobacter clinical isolates; both sulbactam/avibactam and sulbactam/relebactam restored sulbactam activity. A decrease ≥2 dilutions in sulbactam MICs was observed in 89% of the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Some of the knockout strains exhibited a fourfold decrease in the MIC in the sulbactam/zidebactam combination ( Table 2 ). Remarkably, when we compared with previously published results ( Pasteran et al., 2021 ), we observed loss of avibactam enhancement of sulbactam in this knockout strain (AB5075Δ mreB , AB5075 ΔadvA , AB5075 ΔadeB , AB5075 ΔPBPG ), suggesting that the sulbactam/zidebactam combination potentially possesses greater efficiency to inhibit these targets or recognize different target genes.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Some of the knockout strains exhibited a fourfold decrease in the MIC in the sulbactam/zidebactam combination ( Table 2 ). Remarkably, when we compared with previously published results ( Pasteran et al., 2021 ), we observed loss of avibactam enhancement of sulbactam in this knockout strain (AB5075Δ mreB , AB5075 ΔadvA , AB5075 ΔadeB , AB5075 ΔPBPG ), suggesting that the sulbactam/zidebactam combination potentially possesses greater efficiency to inhibit these targets or recognize different target genes.…”
Section: Resultssupporting
confidence: 67%
“…However, against multidrug-resistant (MDR) A. baumannii isolates the efficacy of the current clinical combinations is uncertain. Novel experimental combinations such as sulbactam/avibactam demonstrated promising activity against CRAB with different genetic backgrounds; however, the combination was ineffective against MBL-expressing CRAB ( Rodriguez et al., 2020 ; Pasteran et al., 2021 ). Sulbactam/durlobactam (ETX2514) is also a promising combination in development that has shown very favorable activity against CRAB isolates, except in MBL producers ( Barnes et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rodriguez CH et al [ 47 ] showed that avibactam at a fixed concentration of 4 mg/L reduced the MIC of sulbactam to ≤4 mg/L in all 35 non-metallo-β-lactamase (MBL)-producing sulbactam-resistant A. baumannii isolates in one study. The activity of sulbactam/avibactam (and to a lesser extent of sulbactam/relebactam) was also confirmed in a subsequent study [ 122 ]. The rationale of the combination is that avibactam may inhibit the β-lactamases that affect activity of sulbactam [ 47 ].…”
Section: Resultssupporting
confidence: 57%
“…The rationale of the combination is that avibactam may inhibit the β-lactamases that affect activity of sulbactam [ 47 ]. However, the combination is less effective against metallo-β-lactamase-producing isolates [ 47 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation